Role of Delivery, Course Design and Teacher-Student Interaction: Observations of adult distance education and Traditional on-campus education - Harsh, Om Kumar; Sohail, M. Sadiq (International Review of Research in Open and Distributed Learning, 2002)
This paper provides readers with an observation of an adult distance education programme, which took place in Malaysia. These observations are presented in terms of: study mode, course design, and interaction between three distinct student groups, and their teachers. Other factors that influence adult distance learning melded with traditional classroom settings were also observed. These factors included the demographics of distance learning students, type and nature of student-to-student and teacher-to-student interaction, students’ employment, prior employment, and the subject studied. Our observation suggest that appropriate distance education design, coupled with hybrid opportunities for interaction among students engaged in distance and traditional on-campus modalities, optimise the learning experience of students engaged in both types of learning. Our observations also indicate that factors such as Web-based course design, students’ previous technical competencies and employment history, must also be taken into consideration, when designing and delivering distance education programmes of study. The authors conclude from their observations that further research is needed in terms of proper distance education course design that address environmental factors such as students’ employment history, previous educational experiences, and comfort levels using information and communications technology.